2000
DOI: 10.1021/ja000092s
|View full text |Cite
|
Sign up to set email alerts
|

New Strategies for Organic Catalysis:  The First Highly Enantioselective Organocatalytic Diels−Alder Reaction

Abstract: Over the past 30 years, enantioselective catalysis has become one of the most important frontiers in exploratory organic synthetic research. During this time, remarkable advances have been made in the development of organometallic asymmetric catalysts that in turn have provided a wealth of enantioselective oxidation, reduction, π-bond activation, and Lewis acid-catalyzed processes. 1 Surprisingly, however, relatively few asymmetric transformations have been reported which employ organic molecules as reaction c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
919
2
56

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,581 publications
(992 citation statements)
references
References 10 publications
15
919
2
56
Order By: Relevance
“…2,16 The small energy differences found between the endo and exo orientations of each conformer demonstrated that a distinct preference for one over the other does not occur. This fact is in agreement with the experimentally observed 1:1 endo:exo ratio (predicted endo:exo ratio is 1:1.5 for catalyst 1 and 1.3:1 for catalyst 2 in the gas phase at 25 °C in the case of the alkylation reaction of Nmethyl pyrrole with (E)-crotonaldehyde).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…2,16 The small energy differences found between the endo and exo orientations of each conformer demonstrated that a distinct preference for one over the other does not occur. This fact is in agreement with the experimentally observed 1:1 endo:exo ratio (predicted endo:exo ratio is 1:1.5 for catalyst 1 and 1.3:1 for catalyst 2 in the gas phase at 25 °C in the case of the alkylation reaction of Nmethyl pyrrole with (E)-crotonaldehyde).…”
Section: Resultsmentioning
confidence: 98%
“…This results are also in agreement with the higher enantioselectivity experimentally observed for the endo product (endo 90% ee, exo 86% ee). 2 In 2002 Zora reported the AM1 theoretical study of the cycloaddition reaction of cyclopentadiene with allylidenammonium cation. 38 A stepwise pathway was found, and the activation barrier for the cycloaddition to the C=C bond was 4.2 kcal/mol lower than that to the C=N bond.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2000, MacMillan et al 30 demonstrated that a,b-unsaturated aldehydes could be activated in a face-selective fashion by exposure to the conjugate acids of chiral cyclic secondary amines such as 11 via the formation of an iminium ion 12. Since the condensation is reversible in the presence of trace amounts of water the amine salt could be used in substoichiometric amounts, which quickly led to a new field commonly called 'iminium ion catalysis' (Fig.…”
Section: Iminium Ion Catalysismentioning
confidence: 99%
“…6 Within the field of LUMO catalysis using secondary amines a consistent mechanism has been accepted, the fundamental steps of which are outlined in Figure 1. 7,8,9 In Step 1 the secondary amine salt 1 condenses with the , -unsaturated carbonyl compound 2 to form the reactive iminium ion 3. In…”
Section: Introductionmentioning
confidence: 99%